Dampak Jangka Panjang Merger dan Akuisisi Terhadap Pemegang Saham di BEJ Perbandingan Akusisi Internal dan Eksternal - Sutrisno Sutrisno; Sumarsih Sumarsih (Jurnal Akuntansi dan Auditing Indonesia)
The objective of this research is to understand the long term impact of the internal as well as external merger and acquisition toward shareholder prosperity using size and beta adjust¬ment abnormal return which had already been shown by the study of Dimson & Marsh (1983). This research based on sample of companies that listed on Jakarta Stock Exchange and perform merger and acquisition during 1999-2000. The results show that there is no significant in¬fluence of merger and acquisition toward shareholder prosperity. There isn’t any significant differ¬ent of AAR and CAAR of companies which perform internal as well as external merger and acqui¬sition. Furthermore, the AAR and CAAR of companies before and after merger and acquisition are insignificantly different.